2014
DOI: 10.1007/s00414-014-1128-4
|View full text |Cite
|
Sign up to set email alerts
|

Initial insights into bacterial succession during human decomposition

Abstract: Decomposition is a dynamic ecological process dependent upon many factors such as environment, climate, and bacterial, insect, and vertebrate activity in addition to intrinsic properties inherent to individual cadavers. Although largely attributed to microbial metabolism, very little is known about the bacterial basis of human decomposition. To assess the change in bacterial community structure through time, bacterial samples were collected from several sites across two cadavers placed outdoors to decompose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
107
2
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 35 publications
16
107
2
1
Order By: Relevance
“…37]. As a consequence, the need for comprehensive databases for bacterial populations characteristic of decomposing cadavers and gravesoils were highlighted [5,37]. Our study illustrates the requirement for a similarly rigorous impetus to understand fungal community dynamics in gravesoils, including the use of accessible ecogenomics techniques in protracted further work.…”
Section: Discussionmentioning
confidence: 83%
“…37]. As a consequence, the need for comprehensive databases for bacterial populations characteristic of decomposing cadavers and gravesoils were highlighted [5,37]. Our study illustrates the requirement for a similarly rigorous impetus to understand fungal community dynamics in gravesoils, including the use of accessible ecogenomics techniques in protracted further work.…”
Section: Discussionmentioning
confidence: 83%
“…While other studies of postmortem human microbial communities have included fecal or rectal sampling (e.g., Hyde et al, 2015; Hyde et al, 2013), here we provide an examination of communities in the proximal large intestine (caecum). The bacterial communities in these decomposing individuals had a distinct compositional shift in the middle of the bloat phase of decomposition, between days four and seven in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There has been recent interest in the use of microbial communities in the decomposition environment as markers of PMI: if the postmortem succession of microbial communities is repeatable and predictable, then it may be possible to use the communities as forensic indicators, similar to the approach taken by forensic entomology (Amendt, Krettek & Zehner, 2004). Recent studies have begun describing human postmortem microbial communities associated with a variety of habitats, including skin (Metcalf et al, 2016; Pechal et al, 2017; Hyde et al, 2015), mouth and rectum (Hyde et al, 2015; Hyde et al, 2013), ear and nasal canals (Johnson et al, 2016), internal organs (Javan et al, 2016; Tuomisto et al, 2013), bones (Damann, Williams & Layton, 2015) and soils below (Metcalf et al, 2016; Cobaugh, Schaeffer & DeBruyn, 2015). Other studies have also reported postmortem changes associated with decomposing animal carcasses (Pechal et al, 2013a; Metcalf et al, 2013; Heimesaat et al, 2012; Burcham et al, 2016; Dickson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As decomposition continues, the microbial community changes as bacteria move from sites internal to the body to locations on the surface, and are transferred from the soil, scavengers and insects [15,17,23]. Different species of bacteria are known to be associated with different stages of the decomposition process.…”
Section: Introductionmentioning
confidence: 99%
“…During the bloat stage, Ignatzschineria and Wohlfahrtimonas bacteria are commonly found on the skin of the corpse, and anaerobic bacteria including Lactobacillus and Bacteriodes increase in the abdominal 3 cavity [18]. Microbial communities on a corpse generally become less diverse [23,25] and more similar to each other across body sites [15] with time.…”
Section: Introductionmentioning
confidence: 99%